Phytoplankton and aquatic macroinvertebrate assemblages from coastal and inland lakes of South Africa - Nkibi, Esethu (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Freshwater lakes are generally defined as permanent natural standing water bodies, with some of them having a direct and indirect connection with groundwater, rivers, and the ocean. Freshwater lakes provide essential socio-economic and ecological goods and services including recreation, aesthetic, support aquatic biodiversity, food in a form of fisheries and water for domestic use. Given their critical role in sustainability in providing socio-economic services, freshwater lakes are among the most threatened ecosystems globally due to intense human impacts over the last decades. South Africa has limited freshwater lakes, which according to the National Biodiversity Assessment (NBA 2018), we know little about their current biology except historic aquatic biodiversity studies conducted in the early 1940s. There are no management strategies in place to protect and conserve freshwater lake biodiversity and important ecosystem services. This thesis aims to: (1) produce a biodiversity inventory of phytoplankton and aquatic macroinvertebrate species and, (2) investigate important environmental drivers responsible for phytoplankton and aquatic macroinvertebrate species composition from six South African freshwater lakes. It was hypothesized that the three lake types will show different phytoplankton and aquatic macroinvertebrates species composition attributed by the geographical region (coastal and inland lake) and related physico-chemical parameters. Study sites consisted of two Northern KwaZulu-Natal coastal lakes (hereafter Coastal Lakes, CL) i.e., Lake Sibaya, Lake Mzingazi; two fresh inland lakes (hereafter Fresh Inland Lakes, FIL) i.e., Lake Banagher fresh and Lake Tevrede Se Pan; and two inland salt lakes (hereafter Salt Inland Lakes, SIL) i.e., Lake Banagher salt and Lake Chrissiesmeer, all inland lakes are situated in Mpumalanga province, together with other Pans making up the Mpumalanga Lake District of South Africa. The study sites were categorized based on their geographical position i.e., coastal vs inland and physico-chemical characteristics i.e., the presence and absence of aquatic vegetation, dominate substrate, salinity and different physico-chemical concentration i.e., Temperature, Dissolved Oxygen. Aquatic macroinvertebrates were collected from four littoral zone sites (< 1-meter depth) around each lake, whereas phytoplankton samples were collected from four water column sites (> 5-meters depth) and (0.5-meter depth) from the water surface at each lake during summer and winter season. The results were consistent with our hypothesis that both phytoplankton and aquatic macroinvertebrate species composition were influenced by physico-chemical parameters and that the differences in salinity concentration and aquatic vegetation between CL, FIL, and SIL were the driving factors for phytoplankton and aquatic macroinvertebrate species composition. In summary, one hundred and twenty-two phytoplankton taxa were collected and identified during this study, belonging to seven Phyla which included Chlorophyta, Bacillariophyta, Cyanophyta, Chrysophyta, Dinophyta, Euglenophyta, and Cryptophyta. The most abundant phytoplankton groups were Bacillariophyta and Chlorophyta. Phytoplankton relative taxa abundance, Pielou's evenness, taxa richness, and Shannon diversity were significantly different between lake types. Aquatic macroinvertebrates, on the other hand, summed up to 10 orders, 67 families, and 80 taxa. The most abundant group were the order Coleoptera, Hemiptera, Odonata, and Gastropoda. Aquatic macroinvertebrate relative taxa abundance, taxa richness, and Shannon diversity were also significantly different between lake types. Aquatic macroinvertebrate relative taxa abundance, Pielous evenness, and Shannon diversity index were not significant between seasons, and only taxa richness was significant. Canonical analysis of principal coordinates (CAP) results further showed unique and distinct phytoplankton and aquatic macroinvertebrates community composition between lake types. The present study provides baseline biodiversity inventory (or species list) for important lake ecosystems biological indicators i.e., phytoplankton and aquatic macroinvertebrates and species composition in relation to lake type for six freshwater lakes in South Africa. Furthermore, the study provides empirical evidence that will inform policy and the development of management strategies for freshwater lakes in South Africa which is currently missing. The current study will also contribute to the next National Biodiversity Assessment Report (2024), concerning the freshwater lakes biological data deficiency noted in the previous NBA (2018) report. The study will also fill up the gaps to better understand species composition in lake systems and how they function which is currently limited.
Keywords: Aquatic biodiversity -- South Africa; Indicators (Biology); Lakes -- South Africa; Physicochemical process; Salinity; Phytoplankton; Aquatic macroinvertebrates